Antibacterial potential of Nidus vespae built by invasive alien hornet, Vespa velutina nigrithorax, against food‐borne pathogenic bacteria. Issue 1 (2nd January 2020) - Kim, Jaewon; Kim, Minyoul; Lee, Mijeong; Lee, Yeon‐Jung; Kim, Hak‐Ryul; Nam, Ju‐Ock; Choi, Moon Bo; Hahn, Dongyup
Abstract: The yellow‐legged hornet, Vespa velutina nigrithorax, is an invasive social wasp found in temperate regions and is recognized as a hazardous insect, as it often attacks humans and honeybees. Nidus vespae (nests of social wasps) are traditionally used as a medicinal ingredient; thus, V. v. nigrithorax may be useful as a biological resource. Extracts of Nidus vespae built by V. v. nigrithorax were examined for their antibacterial activity screening against six food‐borne pathogenic bacteria, and the ethyl acetate and butanol layer of the extract exhibited inhibitory activity against the pathogenic bacteria. We determined the antibacterial activity of Nidus vespae built by V. v. nigrithorax for the first time.